2021
DOI: 10.1080/10903127.2021.1967534
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate Air Medical Services Utilization and Recommendations for Integration of Air Medical Services Resources into the EMS System of Care: A Joint Position Statement and Resource Document of NAEMSP, ACEP, and AMPA

Abstract: Air medical services involves providing medical care in transit while using either fixed wing (airplane) or rotor wing (helicopter) aircraft to move patients between locations. The modern use and availability of air medical services has expanded access to various health system resources, including specialty care. While this is generally beneficial, such A c c e p t e d M a n u s c r i p t expansion has also contributed to the complexity of health care delivery systems.(1, 2) Since the publication of the 2013 j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 147 publications
0
7
0
Order By: Relevance
“…Although relationships between EMS findings that are similar to individual criteria of the 201 CDC Guidelines (i.e., prehospital index, high velocity impact, and EMT judgment) and trauma center need have been reported (Lavoie et al, 2010; Mulholland et al, 2008), we believe this finding relating two or more positive steps from the 2011 CDC Guidelines for Field Triage of Injured Patients and hospital outcomes has not been reported previously and has the potential to guide revisions of trauma triage protocols, especially related to destination and transport decisions for patients in remote regions. As has been suggested by others (Lyng et al, 2021), the high mortality rate of patients with two or more positive steps may suggest a need—for patients in remote locations—for early stabilization by air medical or nondesignated hospital teams prior to long-distance transport to a designated trauma center. More study is necessary.…”
Section: Discussionmentioning
confidence: 76%
“…Although relationships between EMS findings that are similar to individual criteria of the 201 CDC Guidelines (i.e., prehospital index, high velocity impact, and EMT judgment) and trauma center need have been reported (Lavoie et al, 2010; Mulholland et al, 2008), we believe this finding relating two or more positive steps from the 2011 CDC Guidelines for Field Triage of Injured Patients and hospital outcomes has not been reported previously and has the potential to guide revisions of trauma triage protocols, especially related to destination and transport decisions for patients in remote regions. As has been suggested by others (Lyng et al, 2021), the high mortality rate of patients with two or more positive steps may suggest a need—for patients in remote locations—for early stabilization by air medical or nondesignated hospital teams prior to long-distance transport to a designated trauma center. More study is necessary.…”
Section: Discussionmentioning
confidence: 76%
“…3 According to the 2021 update to the 2013 joint position statement of the National Association of EMS Physicians, American College of Surgeons, and Air Medical Physician Association, research has shown that patient benefit is gained from the clinical care capabilities of air medical transport independent of potential time saved when transporting patients. 4 These associations use current available evidence to provide guidance for air medical transport utilization. Three major categories that an air medical transport program must consider are clinical care, safety, and quality assurance (QA).…”
Section: Advantages and Benefitsmentioning
confidence: 99%
“…Paramedics will also need all the certifications: ACLS, BLS, PALS, PHTLS, or ITLS. 4 Staff also require a higher level of training to include physiological aspects of flight and how the patient will be affected. Aviation staff will follow Federal Aviation Administration regulations and their program's regulations.…”
Section: Medical Staff/crew Compositionmentioning
confidence: 99%
See 2 more Smart Citations